Peptídeos derivados da toxina ParE: síntese, estrutura e estudos de inibição de DNA topoisomerases - Rocha, Camila Aguiar [UNESP] (2014)
The toxin-antitoxin system ParE-ParD is a bacterial system of post-segregational death encoded in a wide range of hosts. ParE is a small protein of approximately 12 kDa encoded by parE gene. ParD is an antitoxin about 9 kDa, encoded by the parD gene, able of complexing with ParE and neutralize it. Studies have shown the involvement of the enzyme DNA gyrase in the cell death process by ParE, however, is not available in the literature any evidence of inhibition of this protein on the activity of topoisomerase IV. Although found in a wide variety of micro-organisms, the ParE function has not been fully elucidated and its cytotoxic mechanism remains unknown. Based on the primary structure of the E. coli ParE and the limited data available for this toxin, mimetic peptides were rationally designed aiming at understanding the mechanism of inhibition of ParE on the activity of DNA gyrase, as well as on the topoisomerase IV and human topoisomerase II activities. These peptides sequences were synthesized by solid phase methodology, purified and analyzed by high performance liquid chromatography and characterized by mass spectrometry. The ability of these mimetics to inhibit the activity of topoisomerases was tested by electrophoresis on agarose gel. The peptides that showed better results on the inhibition activity of topoisomerases were ParERM3 and ParEC3 , designed to contain the L61-R100 and L69-R100 amino acids sequence, respectively, found of the C-terminal portion of the ParE structure of Escherichia coli. The LNIES sequence (L101 to S105), when present in the mimetic peptides, attenuated the toxicity of the peptides on topoisomerases activity, probably by interfering in the topoisomerase - peptide interactions. Despite the absence of data in the literature regarding the toxicity of ParE protein on the topo IV and human topo II activities, the peptides ParERM3 and ParEC3 showed better inhibitory activity on these enzymes when compared...